Análise transcricional de Corynebacterium pseudotuberculosis biovar equi, linhagem 258, a partir de montagem ab initio: um enfoque nos processos biológicos dos stimulons ácido, térmico e osmótico - Mariana Passos Santana (2014)
Corynebacterium pseudotuberculosis is a pathogenic bacterium responsible for patologies that may cause losses to livestock. Ulcerative lymphangitis, one of these pathologies, manifests mainly on horses infected by the strain 258 of C. pseudotuberculosis (biovar equi). Aiming a better understanding of the microorganism biology, as well as the dynamic of the gene expression during exponential growth phase, a transcriptional study was realized. Through RNAseq it was possible to identify the transcripts on osmotic stress, acidity, and heat shock, which simulate the environment encountered by the pathogen during the infection process, and compare them to the physiological condition. After sequencing through SOLiD V3 plus, the transcripts were assembly by ab initio methodology and data processed on Blast2go with GO (Gene Ontology) attributions. The CDSs (coding sequences) were organized in each category and GO term through CSI (CoreStlmulon) software, and the biological process category was selected for gene analysis. Among stimulons, a group of genes regulated by a certain environmental condition, acidity stress contributed further for the genic catalog. Genes related to combat against reactive oxygen species and heat shock stress were also identified. The heat shock stimulon involved the HSPs (heat shock proteins) as expression modulators, as well as iron uptake genes and cell wall synthesis. On osmotic stimulon, it was not possible to verify the presence of genes relevant to stress, but genes that may be involved on virulence and pathogen survival were described. Among genes shared on two or three conditions, we highlight fts genes, involved on cell division and cycle, and genes related to osmoprotection synthesis. Coding genes of the proteins MraZ, Trx, TrxR, Dps, ferritin like protein, Drp1 e Drp2 have already demonstrated being relevant on other organisms and, therefore, they may contribute to efficient solutions against C. pseudotuberculosis disease and minimize livestock economic losses.